Peripheral precocious puberty in girls with McCune-Albright syndrome: a case series - Faria, Aline Guimarães; Seraphim, Carlos E.; Tirado-Capistros, Mireia; Montenegro, Luciana R.; Canton, Ana Pinheiro Machado; Souza-Pinto, Nadja Cristhina; Lima Jorge, Alexander Augusto; Gomes, Larissa G.; Argente, Jesús; Martin, Regina Matsunaga; Martos-Moreno, Gabriel A.; Latronico, Ana Claudia; et al. (Archives of Endocrinology and Metabolism, 2025)
To describe the follow-up of girls with peripheral precocious puberty (PPP) due to McCune-Albright syndrome (MAS). Data from 18 females, including anthropometric and reproductive outcomes, were evaluated. Genetic analysis was performed on DNA from peripheral leukocytes via digital PCR. Clinical manifestations of PPP were isolated thelarche, thelarche plus vaginal bleeding, or isolated vaginal bleeding in 44.5%, 33.3%, and 22.2%, respectively, at an early age (3.3 ± 1.6 years). At diagnosis, basal LH and FSH levels were suppressed in 100% and 72.2% of cases, respectively, and estradiol ranged from prepubertal to high levels. The mean bone age advancement was 2.3 ± 1.9 years. Treatment included medroxyprogesterone acetate, tamoxifen, aromatase inhibitors, and ketoconazole, individually or in combination for 5 ± 2.14 years, with partial or complete control of puberty. Secondary central precocious puberty was diagnosed in 57.1% (8/14) of the patients. Fibrous dysplasia was diagnosed in 11 patients and managed with bisphosphonates for those with bone pain. The mean adult height was 155.1 ± 8.7 cm (-1.17 SDS) in 10 patients. Menarche occurred at a mean age of 12.2 ± 1.04 years, 70% reported regular menstrual cycles and only one female desired pregnancy. Genetic diagnosis was established in 52.9% (9/17) of the patients. Medical treatment of PPP was effective in girls with MAS and led to preservation of adult height potential, and reproductive function was normal when patients reached adulthood.